Adolescent Movement Cares About Menstrual Hygiene Management (MHM) - Fayakun Nur Rohmah; Siti Arifah (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Lack of knowledge about The Menstrual Hygiene Management (MHM) and poor water sanitation is a problem in adolescents in Indonesia. This community service activity aims to increase students' knowledge and awareness about MHM. This community service was carried out in October 2019 at SD Muhammadiyah Karangkajen I and SD Muhammadiyah Karangkajen II followed by 25 students from grades IV, V and V. The design of this activity is the provision of training on MKM by providing training modules and applying several learning methods including lectures, discussions, and simulations that begin with pretest and end postest. The results showed there was a difference in the average value of knowledge of students to MKM and statistically significant p<0.05. It is expected that students can do MHM appropriately and provide the right information to friends. Teachers are expected to play an active role in providing information about reproductive health so that students get accurate information